A Rare Case of Retrieval of Level IIIc Fractured Copper Intrauterine Device: A - Vijay, Nikita; Sable, Suraj; Bhalerao , Anuja (Journal of Neonatal Surgery, 2026)
Intrauterine devices (IUDs), both hormonal and non-hormonal, are among the several forms of contraception. Reports of IUD fragments being retained in the intrauterine wall have been noticed and these results highlight the significance of the need to remove IUD carefully by the healthcare professionals. A married 36-year-old woman, P2L2, visited the outpatient department with complaint of pain abdomen. History reveals that a copper IUD was inserted seven years ago postpartum at the time of the patient's second delivery and breakage of CuT threads 2 months back. Initial per speculum examination showed a mild erosion of posterior lip of cervix and inflammatory change on Pap smear. Fragmented CuT embedded in myometrium was diagnosed and confirmed on transvaginal USG and pelvic radiograph which was ultimately extracted with a resectoscope using USG guided hysteroscopy. Practitioners who handle IUD insertion and removal should be aware of this atypical complication. There should be improved communication between healthcare providers and patients regarding the risk of fracture IUD. The significance of meticulous IUD planning, from insertion to removal, is highlighted in this case study.